Peran Pengurus Divisi Pendidikan dalam Meningkatkan Akhlakul Karimah Santri di Pondok Pesantren Manbaul’ulum Assalafiyah Wanayasa Purwakarta - Entang Siti Muliani; Ida Afidah; Parihat Kamil (UNISBA Press, 2024)
Abstract. Today’s youth are ignorant of the social issues around them. Promiscuity, juvenile delinquency,ldruglabuse, and sex are all things that have affected modern teenagers. In the midst of a moral crisis,lthe Islamic Boarding School is a place for moral development. The purpose of the study was to find out the programs in the Boarding School to improve the morals of itslstudents, to find out the role of the board in improving the morals oflits students, and to find out the supportingland inhibiting factors used by the board in improving the morals oflthe students. This research uses descriptivenqualitative methods. Islamic Boarding School programs in improving the morals of its students, namely the program of studying book of akhakullbanin and studying shariyahan activities. The managementlhelps programs and activities that aim to improve akhlakul karimah. Thus, the role of the management is included in the active role category, where hey help their students improve their morals through various activities and supervision. Supporting factors from the santri guardian, and providing comfortable facilities. The inhibiting factors are the students' own culture. Abstrak. Generasi muda saat ini tidak peduli dengan masalah sosial di sekitar mereka. Pergaulan bebas, kenakalanlremaja, penyalah gunaan narkoba, danlseks adalah semua hal yang telah mempengaruhi remaja modern. Ditengah krisis akhlak, Pondok Pesantren sebagai wadah pembinaan akhlak. Tujuan penelitian untuk mengetahui program yang adandi Pondok Pesantren untuk meningkatkanlakhlak santrinya, untuk mengetahui peran pengurusldalam meningkatkan akhlak santrinya, danluntuk mengetahui faktor pendukung danlpenghambat yang digunakan oleh pengurus dalam meningkatkan akhlak santri. Penelitian ini menggunakan metode deskriptif kualitatif. Program-program Pondok Pesantren dalam meningkatkan Akhlak santrinya, yaitu program mengkaji kitab akhakul banin dan mengkajilkegiatan syariyahan. Pengurus membantu lprogram dan kegiatan yang bertujuan untuk meningkatkan akhlakul karimah. Dengan demikian, peran pengurus termasuk dalam kategori peran aktif, dimana mereka membantu santrinya meningkatkan akhlak melalui berbagai kegiatan dan pengawasan. Faktor yanglmendukung dari walilsantri, dan menyediakan fasilitas yang nyaman. Faktor penghambat adalah budaya santri sendiri.